Harmonisasi Hukum Kewarganegaraan, Perkawinan Campuran, dan Hak Waris: Perspektif Komparatif Hukum Perdata dan Islam - Nirmala Suci Paramesti; Afthina Aulya Fatma; Rifa Ardian Fahreza (Majelis: Jurnal Hukum Indonesia, 2025)
Mixed marriages are a social phenomenon that is increasingly prevalent with globalization and mobility between countries. The problems arising from mixed marriages not only concern social aspects but also impact the citizenship status and inheritance rights of the parties. This study aims to analyze the legal consequences of mixed marriages on citizenship and inheritance rights from the perspectives of civil law and Islamic law. The method used is normative-comparative research with a legislative and conceptual approach. The results reveal fundamental differences between civil law and Islamic law in regulating citizenship and inheritance rights in mixed marriages. Civil law emphasizes administrative and national aspects, while Islamic law focuses on religious and lineage aspects. These differences lead to variations in the recognition of citizenship and inheritance of property, potentially creating legal uncertainty for the parties. Therefore, harmonization between civil law and Islamic law is essential to create legal certainty and justice, particularly in the context of inter-national and inter-religious marriages in Indonesia